New Structures, Spectrometric Quantification, and Inhibitory Properties of Cardenolides from Asclepias curassavica Seeds - Rubiano-Buitrago, Paola; Pradhan, Shrikant; Paetz, Christian; Rowland, Hannah M. (Molecules (Basel, Switzerland), 2022)
Cardiac glycosides are a large class of secondary metabolites found in plants. In the genus Asclepias, cardenolides in milkweed plants have an established role in plant–herbivore and predator–prey interactions, based on their ability to inhibit the membrane-bound Na+/K+-ATPase enzyme. Milkweed seeds are eaten by specialist lygaeid bugs, which are the most cardenolide-tolerant insects known. These insects likely impose natural selection for the repeated derivatisation of cardenolides. A first step in investigating this hypothesis is to conduct a phytochemical profiling of the cardenolides in the seeds. Here, we report the concentrations of 10 purified cardenolides from the seeds of Asclepias curassavica. We report the structures of new compounds: 3-O-β-allopyranosyl coroglaucigenin (1), 3-[4′-O-β-glucopyranosyl-β-allopyranosyl] coroglaucigenin (2), 3′-O-β-glucopyranosyl-15-β-hydroxycalotropin (3), and 3-O-β-glucopyranosyl-12-β-hydroxyl coroglaucigenin (4), as well as six previously reported cardenolides (5–10). We test the in vitro inhibition of these compounds on the sensitive porcine Na+/K+-ATPase. The least inhibitory compound was also the most abundant in the seeds—4′-O-β-glucopyranosyl frugoside (5). Gofruside (9) was the most inhibitory. We found no direct correlation between the number of glycosides/sugar moieties in a cardenolide and its inhibitory effect. Our results enhance the literature on cardenolide diversity and concentration among tissues eaten by insects and provide an opportunity to uncover potential evolutionary relationships between tissue-specific defense expression and insect adaptations in plant–herbivore interactions.